Fatores de risco associados à nefrotoxicidade em pacientes Tratados com polimixina B - Moresco, Isabel Cristina (2018)
In the last 20 years, with the emergence of multiresistant gram-negative bacteria, polymyxins, which had fallen into disuse due to their high toxicity, were once again used as an alternative for the treatment of these infections. This antibiotic group is active against most enterobacteria and non-fermenting gram-negative bacteria, ocular, urinary tract, meninges, and bloodstream infections. The recommended dose of polymyxin B (PMB) in patients with normal renal function is 1.5 to 2.5 mg.kg-1.day-1 and the dose can be divided twice. For patients with impaired renal function, it is recommended to adjust the dose according to creatinine clearance. Because nephrotoxicity is the major limiting factor in the use of this class of antibiotics, a retrospective observational study was conducted to identify possible risk factors for the development of acute renal injury (ARF) in patients using the antibiotic PMB. The necessary information was collected to perform the study in medical records, medical prescriptions and results of laboratory tests from the patients who used PMB in a period of 5 years in a Brazilian hospital. Inclusion criteria for the study were: patients over 18 years of age who used intravenous PMB for more than 72 hours. To classify ARI levels, baseline creatinine was calculated by the average of the last five serum creatinine tests before the first dose of the antibiotic. This calculated value and the highest level of serum creatinine during treatment were used to identify and classify renal damage according to the criteria of the RIFLE (Risk, Injury and Failure and Loss and End-stage renal disease) filtration rate. The study included 120 patients, most of them male (89; 74.2%) with an average age of 50 years. The most frequent pre-existing comorbidities were systemic hypertension (50; 41.7%), diabetes mellitus (21; 17.5%), nephropathies (14; 11.7%) and obesity (13; 10.8%). The main infection was pneumonia (35.8%) and the most frequently identified infectious agent was Acinetobacter baumannii (67.9%). PMB treatments were performed for 13 days and the average daily dose was 191.5 mg. The high incidence of mortality in the studied population (46.7%) may be related to the critical clinical status of the patients, because at some point of hospitalization, 111 patients (92.5%) needed intensive care. In the population studied to evaluate risk factors, 12 patients (13.5%) presented risk, 22 (25.0%) injury, 30 (34.1%) renal failure, according to RIFLE criteria. In addition, in the group that patients developed ARF, 51.9% died, whereas in the group that did not present, only 12.5% died. There was a statistically significant difference between the groups that developed or not ARF, for the following variables: treatment time greater than 10 days, accumulated PMB dose, hypoalbuminemia and concomitant use of furosemide. However, the variables that remained in the final multivariate logistic regression model were treatment time greater than 10 days and hypoalbuminemia. Several factors inherent to the patient and the drug are related to ARF and strategies should be created in order to minimize these effects. The monitoring of renal function in all patients, especially those at risk, and the follow-up of the infection to reduce the time of treatment are highlighted.